Negação e diferença em Platão Negation and diference in Plato - Eliane Christina de Souza (Trans/Form/Ação, 2010)
Platão, ao tratar da negação no diálogo Sofista, afirma que sempre que enunciamos o que não é, não enunciamos algo contrário ao que é, mas algo diferente. A negação significa cada parte da natureza da diferença em antítese ao que é. Tal tratamento da negação resulta da necessidade de resolver alguns problemas colocados pelo eleatismo. Propõe-se indicar esses problemas e examinar o tratamento que Platão dá ao não-ser como diferença. Plato, in dealing with negation in the dialogue Sophist, says that when we say what is not, we speak not of something that is the opposite of being, but of something different. Negation means each part of the nature of the difference in antithesis to what is. This treatment of negation results from the need to solve some problems posed by eleatism. It is proposed to indicate these problems and examine the treatment that Plato gives to non-being as difference.